1370. The Impact of Increased Recombinant Zoster Vaccine Use on the Burden of Herpes Zoster Among Adults Aged 50 to 59 Years. (15th December 2022) - Singer, David; Salem, Ahmed; Stempniewicz, Nikita; Ma, Siyu; Poston, Sara; Curran, Desmond
Abstract: Background: Recombinant zoster vaccine (RZV) was approved by the Food and Drug Administration for prevention of herpes zoster (HZ) in adults aged ≥50 years in 2017 and recommended for this population by the Advisory Committee on Immunization Practices (ACIP) in 2018. Since the ACIP recommendation, vaccination rates have been increasing but are suboptimal for adults aged 50-59 years compared to adults aged ≥50 years overall. The objective of this study was to model the change in outcomes associated with improved vaccination rates in this population. Methods: A multicohort Markov model was used to compare a scenario using the real-world vaccination rate for adults in the US aged 50-59 years in 2020 to a scenario assuming a higher vaccination rate based on that of adults aged 60-64 years in 2020. Outcomes, based on a lifetime horizon, included HZ cases and complications averted, quality-adjusted life-years (QALY), and costs. Model inputs, including age-specific HZ epidemiology, RZV efficacy, real-world RZV series completion, utilities, and costs (direct and indirect), were based on published literature and US sources. The size of the population aged 50-59 years was based on 2020 US census estimates. Schematic overview of Markov model structure HZ: herpes zoster; PHN: postherpetic neuralgia Results: For the 43 million adults aged 50-59 years, increasing the percentage who received at least one dose of RZV from the current estimate of 7.3% in 2020 to 14.6%, assuming 80% series completion, could avoid an additional 504, 468 HZ cases. An estimated additional 42, 077 post-herpetic neuralgia cases and an additional 56, 247 other complication cases of HZ could be avoided. Based on the estimated cases and complications avoided, an additional 5, 230 discounted QALYs would be gained. Direct costs could be reduced by an additional $638 million (M) and indirect costs by $493M. With incremental vaccination costs of approximately $1, 032M, from a societal perspective, cost savings of $99M would be realized. Conclusion: Increasing RZV vaccination among adults aged 50-59 years could reduce the burden associated with HZ cases, complications, and result in fewer QALY losses. From a societal perspective, cost savings could be achieved in this population in addition to improved clinical outcomes. These findings demonstrate the potential value of increasing RZV vaccination for adults in the US aged 50-59 years. Disclosures: David Singer, PharmD, MS, The GSK group of companies: Employed|The GSK group of companies: Stocks/Bonds Ahmed Salem, MSc, The GSK group of companies: Employed Nikita Stempniewicz, MSc, The GSK group of companies: Employed Siyu Ma, PhD, MBBS, The GSK group of companies: Grant/Research Support Sara Poston, PharmD, The GSK group of companies: Employed|The GSK group of companies: Stocks/Bonds Desmond Curran, PhD, The GSK group of companies: Employed|The GSK group of companies: Stocks/Bonds.